Analysis of the Impact of Mobile Application Implementation and Social Media on Increasing Tourist Visits in Yogyakarta - Setiadi, Bekti; Setiawati, Rahmi; Manalu, Margareta; Dewantara, Rizki; Vandika, Arnes Yuli (West Science Interdisciplinary Studies, 2024)
This study analyzes the impact of mobile application implementation and social media usage on increasing tourist visits in Yogyakarta using a quantitative approach. A total of 200 participants, selected through random sampling, provided responses on a Likert scale ranging from 1 to 5. Data were collected via structured questionnaires and analyzed using SPSS version 26. The findings reveal a significant positive correlation between the utilization of mobile applications and social media and the increase in tourist visits. The results suggest that enhanced digital engagement through these platforms can effectively boost tourism in Yogyakarta, providing valuable insights for stakeholders in the tourism industry to optimize their digital marketing strategies.